2011
DOI: 10.4067/s0718-221x2011000200001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of selected preservatives in protecting Ugandan grown Eucalyptus grandis wood against termite attack

Abstract: Termites are one of the major wood destroying agents in the tropics and with the increasing rate of deforestation, there is a need to protect wood from biodegradation in order to extend its service life. In this study the incidence and severity of termite attack on Eucalyptus grandis sapwood treated with CCA, used engine oil and neem extract were investigated. Sixty samples (20 × 20 × 300mm) were prepared from the sapwood at mid-height of the tree of E. grandis and air seasoned for two weeks then treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 4 publications
1
26
0
4
Order By: Relevance
“…Mattos et al (2013) comparing the effect of the preservative treatment of eucalyptus wood with CCB and burnt oil, concluded that the oily product is efficient given the similarity between the mass loss values of the wood submitted to field tests. Likewise, Ssemaganda et al (2011) Figura 3. Equações ajustadas para a estimativa da perda de massa (PM) das madeiras de amescla em função do tempo (t) de exposição ao ensaio de campo.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Mattos et al (2013) comparing the effect of the preservative treatment of eucalyptus wood with CCB and burnt oil, concluded that the oily product is efficient given the similarity between the mass loss values of the wood submitted to field tests. Likewise, Ssemaganda et al (2011) Figura 3. Equações ajustadas para a estimativa da perda de massa (PM) das madeiras de amescla em função do tempo (t) de exposição ao ensaio de campo.…”
Section: Resultsunclassified
“…Although is not a commercial preservative product, the use of burnt oil of combustion engines has been highlighted by some authors (OLANIRAN et al, 2010;SSEMAGANDA et al, 2011;MATTOS et al, 2013;GALLON et al, 2014) as being effective for increasing the biological resistance of wood. Also, Omole;Onilude (2000) and Mattos et al (2012) recommended the use of burnt oil as being a residue of the automotive industry which can be obtained at low cost and which does not require the use of industrial methods for wood impregnation.…”
Section: Introductionmentioning
confidence: 99%
“…Embora não seja reconhecido como um preservativo de madeira, Olaniran et al (2010) e Ssemaganda et al (2011) destacam que o aproveitamento de óleo queimado de motores de combustão pode fornecer aumento na resistência ao ataque de organismos xilófagos. De acordo com Mattos et al (2013) o emprego do óleo queimado de motor, em especial para preservação de mourões, cercas e pequenas estruturas rurais, apresenta como atrativo a facilidade de manipulação, sem necessidade de aplicação de pressão, e o baixo preço de aquisição.…”
Section: Introductionunclassified
“…Perda de massa das madeiras tratadas em diferentes tempos de imersão simples. Ssemaganda et al (2011) também verificaram resultados satisfatórios com a aplicação de óleo queimado, por meio do método de imersão, em madeiras de Eucalyptus grandis, não havendo indícios de ataque de térmitas após 8 meses de exposição em ensaios de deterioração de laboratório.…”
unclassified
“…Wood materials damaged by insects result in both technical and economic losses (Ssemaganda et al 2011). Over the past 60 years, numerous synthetic insecticides have been developed and used.…”
Section: Introductionmentioning
confidence: 99%